A Quality Improvement Collaborative for Adolescents Living With HIV to Improve Immediate Antiretroviral Therapy Initiation at 25 Health Facilities in Lusaka, Zambia. (21st November 2021) - Dougherty, Gillian; Boccanera, Rodrigo; Boyd, Mary Adetinuke; Gantt, Tracey; Chilungu Kasonka, Siphiwe; Kasonde, Prisca; Kaetano, Nila; Madevu-Matson, Caitlin; Milimo, Phales; Mwamba, Mukuka; Panya, Milembe; Senyana, Brenda; et al.
Abstract: HIV testing with rapid antiretroviral therapy (ART) initiation are life-saving interventions for adolescents living with HIV. However, in Zambia, HIV diagnosis and immediate ART initiation among adolescents living with HIV is lagging. In collaboration with the Zambian Ministry of Health, the U.S. Health Resources and Services Administration, the U.S. Centers for Disease Control and Prevention in Zambia, and ICAP at Columbia University designed and implemented a quality improvement collaborative (QIC) to improve adolescent immediate ART initiation at 25 health facilities in Lusaka. Over the 12-month implementation period, quality improvement teams tested and identified targeted intervention, that significantly improved ART initiation within 14 days of receiving positive test results, from 24% at baseline to more than 93% for the final 6 months of implementation. The quality improvement collaborative approach empowered health care workers to innovate addressing the root causes of suboptimal performance and produced a package of successful interventions that will be shared throughout Zambia.